Design and analysis of 33-bus solar based MLDG distribution system - Vimal Katiyar, Mohd Ilyas, A.S.Azad (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Demand of energy increases day by day, to meet the energy demand it is the time to shift towards renewable sources, (solar energy, wind energy, tidal energy, bio-mass energy etc.). Renewable energy attract interest of researcher due to its environment friendly nature . At the large scale of renewable energy generation, power quality into the grid is an important parameter. In this paper area of focus is the design and analysis of IEEE-33 bus solar based MLDG (multiple location distributed generator) system with maximum penetration in grid with operational scenarios of LV network. The main aim of this paper is to design a MLDG IEEE 33- bus system for rural location of United Kingdom of Saudi Arabia with reduced power loss and improved voltage profile with economic benefits. In this proposed model DGs (distributed generators) are placed at multiple locations to enhance the performance of hybrid solar system with respect to improve power quality and reduced power losses.